(untitled) (Patrimônio e Memória, 2018)
This article aims to analyze the names of housing estates in the city of Londrina, especially those built under the National Housing Bank - BNH - (1967 to 1986), during the period of the Military Dictatorship in Brazil. From the theoretical reference of Ulpiano T. B. de Meneses, we turn our gaze to the city as a place of analyzes of sociability, an artifact constructed from different interests. In addition, we surrounded ourselves by the concept of memory, especially by Jacques Le Goff, to analyze the names of housing estates and honored personalities comprising memory as an element of disputes. Thus, based on the study of toponymy, we investigate the urban space as a field of study about memories and identities, seeking to reveal the ways in which urban collective memory is constituted, based on the political, economic and ideological interests.